2003
DOI: 10.1128/aem.69.8.4760-4769.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Streptococcus mutans Strains Deficient in EIIAB Man of the Sugar Phosphotransferase System

Abstract: The phosphoenolpyruvate:sugar phosphotransferase system (PTS) is the major sugar uptake system in oral streptococci. The role of EIIAB Man (encoded by manL) in gene regulation and sugar transport was investigated in Streptococcus mutans UA159. The manL knockout strain, JAM1, grew more slowly than the wild-type strain in glucose but grew faster in mannose and did not display diauxic growth, indicating that EIIAB Man is involved in sugar uptake and in carbohydrate catabolite repression. PTS assays of JAM1, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 43 publications
3
113
2
Order By: Relevance
“…In CD630, gntR was upstream of genes encoding the mannose-specific phosphotransferase system (PTS) (Sebaihia et al, 2006). The mannose PTS is involved in sugar transport and global regulation of gene expression, in a number of Gram-positive genera (Abranches et al, 2003;Arous et al, 2004;Chaillou et al, 2001;Reizer et al, 1999), including the regulation of energy metabolism and virulence genes in Streptococcus mutans (Abranches et al, 2006). Hypothetically, integration of wC2 into CD630 could lead to significant changes in the C. difficile phenotype through mannose PTS deregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In CD630, gntR was upstream of genes encoding the mannose-specific phosphotransferase system (PTS) (Sebaihia et al, 2006). The mannose PTS is involved in sugar transport and global regulation of gene expression, in a number of Gram-positive genera (Abranches et al, 2003;Arous et al, 2004;Chaillou et al, 2001;Reizer et al, 1999), including the regulation of energy metabolism and virulence genes in Streptococcus mutans (Abranches et al, 2006). Hypothetically, integration of wC2 into CD630 could lead to significant changes in the C. difficile phenotype through mannose PTS deregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Using 2D gels, many alterations in expression of cytoplasmic and membrane proteins were observed in these mutants. More recently, it was shown that EIIAB Man plays a role in CCR by regulating diauxic growth in S. mutans and S. salivarius (Abranches et al, 2003;Pelletier et al, 1998;Vadeboncoeur and Pelletier, 1997). In S. mutans, EIIAB Man can also regulate the activity of other sugar-specific EII enzymes, as well as the expression of important virulence genes, including gtfBC and ftf (Abranches et al, 2003).…”
Section: Living the Feast-or-famine Existence: Carbohydrate Source Anmentioning
confidence: 99%
“…Of note, elegant studies from the Burne group on carbon metabolism and carbon catabolism repression revealed a highly complex, hierarchical and efficient control of energy generation by S. mutans, and also indicated that carbon metabolism is intertwined with the expression of virulence-related traits (Abranches et al, 2003(Abranches et al, , 2008Zeng et al, 2006).…”
Section: S Mutans Is the Bacterial Paradigm Of Lactic Acid Bacteria mentioning
confidence: 99%